2021
DOI: 10.1016/j.nima.2021.165411
|View full text |Cite
|
Sign up to set email alerts
|

Practical tests of neutron transmission imaging with a superconducting kinetic-inductance sensor

Abstract: Samples were examined using a superconducting (Nb) neutron imaging system employing a delay-line technique which in previous studies was shown to have high spatial resolution. We found excellent correspondence between neutron transmission and scanning electron microscope (SEM) images of Gd islands with sizes between 15 and 130 μm which were thermally-sprayed onto a Si substrate. Neutron transmission images could be used to identify tiny voids in a thermally-sprayed continuous Gd2O3 film on a Si substrate which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…We confirmed that the energy resolution is good enough to obtain the resonance absorption dips to reveal mosaic crystalline structure appeared in Sm-Sn mixed metal [19]. In order to check the practical usefulness of the CB-KID imaging, we demonstrated a good linearity between the Gd-island sizes obtained from neutron transmission images and those obtained from SEM images over a wide length range from 20 μm to 130 μm [20].…”
Section: Introductionsupporting
confidence: 65%
See 1 more Smart Citation
“…We confirmed that the energy resolution is good enough to obtain the resonance absorption dips to reveal mosaic crystalline structure appeared in Sm-Sn mixed metal [19]. In order to check the practical usefulness of the CB-KID imaging, we demonstrated a good linearity between the Gd-island sizes obtained from neutron transmission images and those obtained from SEM images over a wide length range from 20 μm to 130 μm [20].…”
Section: Introductionsupporting
confidence: 65%
“…The size of needles is the minimum width of 25 um (see the inset of figure 3(a) for zoomed image) and the length up to 4.5 mm. In our previous work [20], we identified very fine needle patterns of 10-m width using the Wood's metal sample while the image was obtained by placing a sample at the cryogenic temperature. This is to avoid the blurring of the image to placing the sample at the very vicinity of the neutron detector.…”
Section: Sample Preparationmentioning
confidence: 99%
“…A delay-line technique of the four-terminal CB-KID successfully achieved neutron imaging with a spatial resolution of 16 μm [5]. We observed neutron transmission images of practical Gd islands with various sizes and thicknesses with CB-KID and demonstrated that the neutron transmission images of various Gd islands were in good agreement with the scanning electron microscope (SEM) images [7]. Since thermal and cold neutrons behave like waves, they inform the wavelength-sensitive interference properties of materials through the Bragg diffraction, i.e., the Bragg edges in the neutron transmission spectra can be observed by coherent scattering in crystalline materials.…”
Section: Introductionmentioning
confidence: 69%
“…The superconducting neutron sensor in this study exhibited a high spatial resolution [5,7]. This study aimed to determine how narrow we can select a testing area to obtain a visible Bragg edge using an iron test sample with CB-KID.…”
Section: Resultsmentioning
confidence: 99%